The Alignment of Assessment Tasks with Teaching Objectives and Activities Based on Bloom Taxonomy: Case Study - Nazelya Puspita Kencana; Oikurema Purwati; Ahmad Munir (ELT Worldwide: Journal of English Language Teaching, 2022)
Assessment plays an important role in teaching process to show students’ understanding and comprehension about the material. Good assessment task is the one which can achieve the teaching objective. Then, this research discusses about the alignment of assessment task with teaching objectives and activities on Junior High School Teacher’ lesson plan based on Bloom Taxonomy. This study uses qualitative descriptive which focuses on document analysis. In getting the data, the researcher asked the Junior High School Teacher’s lesson plan and analyzed each components based on Taxonomy Table. The results highlighted that the assessment tasks which Junior High School teacher designed do not align with teaching objectives and activities since the teacher did not break down the objectives properly even though the analysis on the Taxonomy Table shows good alignment. Further discussion is elaborated in this research.